2020
DOI: 10.21203/rs.3.rs-18581/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Problems in measuring the JTC-bias in patients with psychotic disorders with the fish task: A secondary analysis of a baseline assessment of a randomized controlled trial

Abstract: Background: The jumping to conclusions bias (JTC) is considered to be an important causal factor in theoretical models on the formation and maintenance of delusions. However, recent meta-analytic findings show a rather equivocal pattern of results regarding associations between JTC and delusions. Thus, the aim of the present preregistered study is to investigate in a large sample whether the JTC-bias is more pronounced in patients with psychotic disorders in comparison to controls and whether the JTC bias is a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Patients with SCZ consistently show JTC 1,4,11 and over-estimate the probability that the beads are drawn from a specific jar 9,10,[12][13][14] . However, the reasons for this bias remain unclear 1,4,11,[15][16][17][18] . On the one hand, JTC has been associated with delusions 1-4, 11, 19-23 and impulsive decision-making 1,2,22,24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with SCZ consistently show JTC 1,4,11 and over-estimate the probability that the beads are drawn from a specific jar 9,10,[12][13][14] . However, the reasons for this bias remain unclear 1,4,11,[15][16][17][18] . On the one hand, JTC has been associated with delusions 1-4, 11, 19-23 and impulsive decision-making 1,2,22,24 .…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, JTC has been associated with delusions 1-4, 11, 19-23 and impulsive decision-making 1,2,22,24 . On the other hand, a growing number of studies have shown that patients with SCZ display JTC even without the presence of delusions and other authors have attributed JTC to impaired probabilistic reasoning 10,11,16,18,[25][26][27] . Specifically, patients seem to overweight unexpected recent bead occurrences -leading to unstable beliefs about the correct source jar 9,12,15,17,28 .…”
Section: Introductionmentioning
confidence: 99%